Trend Ekspor Komoditas Perkebunan di Indonesia - Ibrahim, Noer Ibrah; Syafiuddin, Syafiuddin; Akhmad, Akhmad; Natsir, Mohammad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Plantation commodities have an important role in the country's foreign exchange earnings due to the high performance of its leading commodity exports. This study aims to analyze the trend in the volume and value of plantation commodity exports (palm oil, rubber, cocoa) in Indonesia during the period 2019-2023. The coverage area in this study is Indonesian data. The type of data used is secondary data of annual time series in the period 2019 to 2023. The main data sources were obtained from the Central Statistics Agency (BPS) and the Ministry of Agriculture. The data analysis used linear trend analysis with the ordinary least square method. The results of this study indicate that the trend in the volume of palm oil commodity exports in Indonesia during the period 2019-2023 has a downward trend of 562.17 million tons per year, while in the same period the trend in the value of palm oil exports has an increasing value of up to 2,586.2 million US$ per year. The trend of rubber commodity export volume in Indonesia during that period has a tendency to decrease by 223.18 million tons per year, while the trend of rubber export value has a tendency to decrease to reach 224.49 million US$ per year. The trend of cocoa commodity export volume in Indonesia during the last five years has a tendency to decrease by 19.17 million tons per year, while the trend of cocoa export value has a tendency to decrease to reach 8.12 million US$ per year.